Targeting CDK4/6 pathways and beyond in breast cancer. (February 2019) - Ribnikar, Domen; Volovat, Simona Ruxandra; Cardoso, Fatima
Abstract: Metastatic or advanced breast cancer (mBC/ABC) remains incurable despite many different systemic treatment options. Hormone receptor positive (HR+) disease represents the most common subtype in both early and advanced disease. A better understanding of the biology of this BC subtype, in particular regarding potential mechanisms of endocrine resistance, has led to the development of CDK4/6 inhibitors. All three selective CDK4/6 inhibitors, palbociclib, ribociclib and abemaciclib have shown to significantly improve progression-free survival (PFS) when combined to endocrine therapy as first-line treatment for patients with HR+/HER-2 negative ABC, who have progressed on or after adjuvant endocrine therapy. All three of them have also shown an improved PFS as 2nd line therapy for HR+/Her2 negative ABC. Their toxicity profile is favorable, with hematological toxicity (mainly neutropenia) being predominant, followed by diarrhea and fatigue. Quality of life has been maintained in the 1st line setting or improved in the 2nd line setting. Overall survival (OS) has been reported so far only in 2 out of 7 trials as first line therapy and the difference did not reach statistical significance. In this article we review the biology of CDK signaling pathway and its inhibitors, preclinical and clinical data of all three investigated selective CDK4/6 inhibitors and their toxicity. We also discuss how these agents are being included in current international guidelines and future directions for these agents in other subtypes of breast cancer, in both advanced disease and early-stage disease. Highlights: A better understanding of endocrine resistance of HR-positive HER-2-negative ABC, has led to the development of CDK4/6 inhibitors. Palbociclib, ribociclib and abemaciclib have shown to significantly improve PFS when combined to ET as first or second line treatment for patients with HR+/HER-2 negative ABC. Quality of life of patients seems to be good with low toxicity. Data on OS will be available soon. Currently, there are no known tissue or blood biomarkers that can predict benefit from CDK4/6 inhibition. Further biomarker analyses are indispensable to better select patients who derive the greatest benefit from CDK4/6 inhibitors, in both early and advanced settings. There are many unanswered questions in the management of HR+/HER-2 negative ABC, namely what is the best sequencing of all available treatment options, how do combinations of CDK4/6 inhibitors + ET and mTOR inhibitors + ET compare with each other and with chemotherapy. Improved knowledge of mechanisms of resistance to CDK4/6 inhibitors may in near future help to better tailor subsequent therapy after progression on CDK inhibitors.